Validation of the Official Slovak Version of the Unified Dyskinesia Rating Scale (UDysRS). (2nd July 2015) - Skorvanek, Matej; Minar, Michal; Grofik, Milan; Kracunova, Katarina; Han, Vladimir; Cibulcik, Frantisek; Necpal, Jan; Gurcik, Ladislav; Valkovic, Peter
Abstract : After successful clinimetric testing of the Unified Dyskinesia Rating Scale (UDysRS), a program for translation and validation of non-English versions of the UDysRS was initiated. The aim of this study was to validate and confirm the factor structure of the Slovak translation of the UDysRS. We examined 251 patients with Parkinson's disease and dyskinesia using the Slovak version of the UDysRS. The average age of our sample was 65.2 ± 9.2 years and average disease duration was 10.9 ± 5.0 years. Slovak data were compared using confirmatory factor analysis with the Spanish data. To be designated as the official Slovak UDysRS translation, the comparative fit index (CFI) had to be≥ 0.90 relative to the Spanish language version. Exploratory factor analysis was performed to explore the underlying factor structure without the constraint of a prespecified factor structure. For all four parts of the Slovak UDysRS, the CFI, in comparison with the Spanish language factor structure, was≥ 0.98. Isolated differences in the factor structure of the Slovak UDysRS were identified by exploratory factor analysis compared with the Spanish version. The Slovak version of the UDysRS was designated as an official non-English translation and can be downloaded from the website of the International Parkinson and Movement Disorder Society.